Shipwreck - Platt, Richard; Wilson, Alex; Chambers, Tina (New York : Alfred A. Knopf, 1997)
Describes the history of shipwrecks, famous wrecks, causes, navigation and rescue techniques, and underwater archeology and the exploration of wrecks.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
Keywords: Shipwrecks -- Juvenile literature; Shipwrecks